2019
DOI: 10.1002/jcb.28788
|View full text |Cite
|
Sign up to set email alerts
|

HHEX gene polymorphisms and type 2 diabetes mellitus: A case‐control report from Iran

Abstract: Genome‐wide association studies indicated that hematopoietically‐expressed homeobox (HHEX) gene is a remarkable candidate for type 2 diabetes (T2D) mellitus susceptibility in spite of the fact that the results are ambiguous in some cases. So, this study aimed to evaluate the possible correlation between HHEX gene polymorphisms and T2D development in a sample of the Iranian population. The rs1111875G/A, rs7923837A/G, and rs5015480C/T HHEX gene polymorphisms were genotyped in 250 cases and 250 matched (age and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…Genome-wide association studies indicated that HHET rs1111875G/A and rs5015480C/T variants significantly increased the risk of T2DM. 27 Hamidreza Galavi et al found the SREBF-2 gene rs2267439C/T polymorphism increased T2DM susceptibility. 28 IGF2BP2 rs11705701 and rs1470579 gene polymorphisms may be associated with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide association studies indicated that HHET rs1111875G/A and rs5015480C/T variants significantly increased the risk of T2DM. 27 Hamidreza Galavi et al found the SREBF-2 gene rs2267439C/T polymorphism increased T2DM susceptibility. 28 IGF2BP2 rs11705701 and rs1470579 gene polymorphisms may be associated with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Other comprehensive studies must be performed in order to establish the effect of HHEX on CRC hazard, particularly in several populations [41]. HHEX rs1111875G/A and rs5015480C/T may contribute to the upgrade of T2D hazard in a test of the southeast Iranian population [42].…”
Section: Hhex (Hematopoietically-expressed Homeobox Protein)mentioning
confidence: 99%
“…This involved genes such as glucokinase (GCK) [ 6 ], hepatocyte nuclear factor 1 alpha (HNF1A) [ 7 ], hepatocyte nuclear factor 1 alpha (HNF4A) [ 8 ], hepatocyte nuclear factor 1 beta ( HNF1B ) [ 9 ], sulfonylurea receptor 1 (ABCC8) [ 10 ], Insulin (INS), Neuronal differentiation 1 (NEUROD1) [ 11 ], insulin gene promoter factor 1 (IPF1 or PDX1) [ 12 ], Paired box 4 (PAX4) [ 13 ], ATP-binding cassette sub-family C member 8 (ABCC8), GATA binding protein 4 (GATA4) [ 14 ] and GATA binding protein 6 (GATA6) [ 15 ]. Potassium inwardly rectifying channel, subfamily J, member 11 (KCNJ11) [ 16 ], kruppel-like factor 11 (KLF11) [ 17 ], carboxyl ester lipase (CEL) [ 18 ], B lymphoid tyrosine kinase (BLK) [ 19 ], Adaptor protein, phosphotyrosine interacting with PH domain and leucine zipper 1 (APPL1) [ 20 ] Previous human genetic studies have demonstrated a correlation between the genetic mutations and T2DM, such as lamin A/C mutations [ 21 ], glucokinase regulatory protein (GCKR) [ 22 ], fat mass and obesity-associated gene (FTO) [ 23 ], monocarboxylate transporter 11(SLC16A11) [ 24 ], hematopoietically-expressed homeobox (HHEX) gene [ 25 ], transcription factor 7-like 2 (TCF7L2) [ 26 ], Pro12Ala polymorphism in peroxisome proliferator-activated receptor- γ (PPAR- γ ) [ 27 ] and others. The role of single nucleotide polymorphisms in T2DM is also known.…”
Section: Introductionmentioning
confidence: 99%